Inhibition and Induction by Poziotinib of Different Rat Cytochrome P450 Enzymes In Vivo and in an In Vitro Cocktail Method - Wang, Jinhui; Chen, Feifei; Jiang, Hui; Xu, Jia; Meng, Deru; Geng, Peiwu; Dai, Dapeng; Hu, Jingbo; Zhou, Yunfang; Zhou, Quan; Wang, Shuanghu (Frontiers in Pharmacology, 2021)
Poziotinib is an orally active, irreversible, pan-HER tyrosine kinase inhibitor used to treat non-small cell lung cancer, breast cancer, and gastric cancer. Poziotinib is currently under clinical investigation, and understanding its drug-drug interactions is extremely important for its future development and clinical application. The cocktail method is most suitable for evaluating the activity of cytochrome P450 enzymes (CYPs). As poziotinib is partially metabolized by CYPs, cocktail probes are used to study the interaction between drugs metabolized by each CYP subtype. Midazolam, bupropion, dextromethorphan, tolbutamide, chlorzoxazone, phenacetin, and their metabolites were used to examine the effects of poziotinib on the activity of cyp1a2, 2b1, 2d1, 2c11, 2e1, and 3a1/2, respectively. The in vitro experiment was carried out by using rat liver microsomes (RLMs), whereas the in vivo experiment involved the comparison of the pharmacokinetic parameters of the probes after co-administration with poziotinib to rats to those of control rats treated with only probes. UPLC-MS/MS was used to detect the probes and their metabolites in rat plasma and rat liver microsomes. The in vitro results revealed that the IC50 values of bupropion and tolbutamide in RLMs were 8.79 μM and 20.17 μM, respectively, indicating that poziotinib showed varying degrees of inhibition toward cyp2b1 and cyp2c11. Poziotinib was a competitive inhibitor of cyp2b1 and cyp2c11, with Ki values of 16.18 μM and 17.66 μM, respectively. No time- or concentration-dependence of inhibition by poziotinib was observed toward cyp2b1 and cyp2c11 in RLMs. Additionally, no obvious inhibitory effects were observed on the activity of cyp1a2, cyp2d1, cyp2e1, and cyp3a1/2. In vivo analysis revealed that bupropion, tolbutamide, phenacetin, and chlorzoxazone showed significantly different pharmacokinetic parameters after administration (P < 0.05); there was no significant difference in the pharmacokinetic parameters of dextromethorphan and midazolam. These results show that poziotinib inhibited cyp2b1 and cyp2c11, but induced cyp1a2 and cyp2e1 in rats. Thus, poziotinib inhibited cyp2b1 and cyp2c11 activity in rats, suggesting the possibility of interactions between poziotinib and these CYP substrates and the need for caution when combining them in clinical settings.